When net-zero falls short of carbon neutrality: Assessing dynamic life-cycle carbon integrity in grid-connected building microgrids - Gur, Muhammed; Oztop, Hakan F.; Hepbasli, Arif (Elsevier, 2026)
This study develops an integrated framework coupling the Transient System Simulation Tool (TRNSYS), the Hybrid Optimization Model for Multiple Energy Resources (HOMER) Pro, SimaPro, and hourly carbon accounting to evaluate a U.S. Department of Energy (DOE) Medium Office reference building in Istanbul, Phoenix, Miami, and Stockholm. Hourly building loads generated in TRNSYS are used in HOMER Pro to optimize gridconnected photovoltaic (PV)-lithium-ion battery-converter microgrids under cost-optimal and annual net-zero definitions. SimaPro quantifies the replacement-inclusive embodied impacts of the optimized PV and converter systems. To ensure cross-location comparability, the hourly grid carbon-intensity datasets are harmonized to a direct operational electricity-generation boundary while an identical embodied-LCA system boundary is applied across all locations. Results show that none of the configurations satisfying annual net-zero or annual netexport conditions reached the dynamic life-cycle carbon-neutrality threshold of DNZII >= 1. Istanbul S2 achieved annual net-zero energy balance but reached a DNZII of only 0.765. Miami S2 achieved DNZII values of 0.627 in 2025 and 0.628 in 2030, before declining to 0.219 in 2050. Stockholm S2 also satisfied annual net-zero energy balance but reached a DNZII of only 1.46 & times; 10- 4, because the direct operational carbon values of both imports and exports were negligible relative to the embodied infrastructure burden. A supplementary time-value-ofcarbon sensitivity further reduced all DNZII values; for example, Istanbul S2 decreased from 0.7646 to 0.68 and 0.5763 under carbon discount rates of 3% and 7%, respectively, without changing any neutrality classification. The cost-optimal Phoenix configuration provides the clearest counterexample: despite being an annual net exporter, its DNZII decreased from 0.55 in 2025 to 0.237 in 2030 and 0.0028 in 2050. These results demonstrate that annual net-zero is an energy-accounting condition whereas carbon neutrality requires consistent system boundaries, temporally resolved grid-carbon accounting, and replacement-inclusive embodied life-cycle assessment.
Keywords: Annual Net-Zero Energy; Dynamic Life-Cycle Carbon Neutrality; Building Microgrids; Hourly Grid Carbon Intensity; Life-Cycle Assessment; Dynamic Net-Zero Integrity Index (Dnzii)